The size of excavators within a polymorphic termite species governs tunnel topology - Haifig, Ives [UNESP]; Jost, Christian; Janei, Vanelize [UNESP]; Costa-Leonardo, Ana Maria [UNESP] (Academic Press Ltd Elsevier B.V. Ltd, 2011)
Caste polymorphism in termites may provide specialization for different tasks in a colony, generating a division of labour that promotes fitness. The influence of polymorphism has been widely studied for many termite activities, although general patterns are missing in the literature. The aim of our study was to verify the influence of polymorphism on the tunnelling behaviour of termites and to test how the size of workers influences the network geometry. We hypothesized that larger workers dig fewer and longer tunnels, while smaller workers dig shorter and more ramified tunnels. We tested this hypothesis by separating groups of polymorphic workers of Velocitermes heteropterus according to their size and analysing the topology of their networks. The workers of V. heteropterus were first examined to ensure their dimorphism and then sexed to confirm their sexual polymorphism. The analysis of the tunnel networks showed that major female workers dug faster but with less bifurcations compared to minor male workers. When both types of workers were placed together, the resulting network topology was closer to that of the majors, suggesting that this class may govern the activities during tunnelling. Our results show that worker size influences the network architecture and that, in the case of V. heteropterus, the majors dominate both digging and the bifurcation rate. (C) 2011 The Association for the Study of Animal Behaviour. Published by Elsevier Ltd. All rights reserved.
Keywords: isoptera; Markov process; polymorphism; tunnel network; Velocitermes heteropterus